Analysis of the Phenotypic Adaptability and Stability of Wheat Genotypes through the Biplot Approach - Verma, Ajay; Tyagi, B. S.; Singh, Gyanendra (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during the cropping season during October to April in the year 2022–23. Highly significant effects of environments, genotypes×environments interactions and genotypes had been observed as per the AMMI analysis of twelve wheat genotypes evaluated under advanced varietal trials at eleven major locations and Environments effects had augmented about 49% of the total sum of squares. ASV measure had utilized the 51.7% of the interaction effects had pointed for DBW296, HI1654, PBW899 while MASV measure had exploited nearly 98% of total interaction effects had selected the DBW296, WH1311, UP3111 genotypes as Superiority index measure also the suitability of same genotypes. The simultaneous selection index based on yield and ASV had pointed towards the HI1653, HI1654, HD3369 and genotypes HI1653, DBW397, WH1311 were identified by ssi MASV and genotypes HI1654, HD3369, HI1653 genotypes settled by ssi WAASB measure. Non parametric Si1 had pointed for DBW296, HD3369, NIAW3170 and the values of Si2 and Si3 had pointed towards DBW296, WH1311, HD3369. Composite non parametric measures First measure NPi(1) had favoured the DBW296, HI1653, HD3369 while as per NPi(2) values the DBW296, NIAW3170, PBW899 would be suitable genotypes. Out of the five clusters in the biplot analysis the ASV & WAASB had clustered with NPi(1), Si2, Si3, Si4, Si5, Si6, Si7 non parametric measures as placed in the first quadrant.